A Perception of Tourism Student Towards Job Opportunity: Learning Foreign Language as Competence: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Mastering a foreign language can hone your comprehension and communication skills. Learning a foreign language will help every student open new job opportunities, especially in the tourism and hospitality industry. It will also enhance your perception of new things, especially the cultures and traditions of the people using your chosen language.   This study used a qualitative design research method to find out. The researchers analyzed the challenges encountered in the good work they would do for the students of Best Link College in the Philippines. Sixty percent of student Tourism researchers are confident that this number accurately represents the entire population, and the selected respondents will do their best to answer the questionnaire responsibly. This study used two statistics Tools: Frequency and percentage and weighted mean. Every Bestlink College of the Philippines tourism student must learn a foreign language. To encourage specific objective: to encourage people that every student should learn a foreign language. The main idea is that learning a foreign language enhances communication skills. Learning a foreign language enhances job and career opportunities.
Keywords: Learning a foreign language; competency